Calvin Benjamin papers - Benjamin, Calvin, -1847.
Chiefly correspondence, along with transcribed excerpts and notes, relating to Benjamin's service under Gen. Zachary Taylor during the Mexican War. Also documents Benjamin's assignment with the United States Coast Survey on the Chesapeake Bay. Includes letters (1849-1851) written by his brother, Judson Benjamin, while serving as a Baptist missionary in Burma.
U.S. Army officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Benjamin, Judson. -- Correspondence; Taylor, Zachary, -- 1784-1850.; United States. -- Army -- History -- Mexican War, 1846-1848.; United States Coast Survey; Baptists -- Missions -- Burma; Mexican War, 1846-1848.; Chesapeake Bay (Md. and Va.); Army officers